2017
DOI: 10.1002/cae.21795
|View full text |Cite
|
Sign up to set email alerts
|

Educational framework for a motor drive control systems: Design and performance assessment

Abstract: In this paper, an emulation based electrical drive laboratory for graduate and undergraduate power engineering students and practicing engineers is presented. The virtual laboratory is realized by means of Hardware‐In‐the‐Loop (HIL) system, which is increasingly recognized as an effective approach in the design of power electronics control. Control of induction motor, as the most widely used machine including main and side effects is examined. In order to perform experiments gradually, software development fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…These speed variations determine the speed and torque to be supplied by the electrical motor. This is done through a throttle sensor, which receives the speed signal operated by the driver and establishes a voltage reference value in the pulse width modulation (PWM) control, to control the desired speed and torque of the motor [24]. The electrical power is provided by a pack of six‐lead acid batteries connected in series, and it is transferred to the mechanical system through a drive axle gearbox, which links the electrical and mechanical power systems in the powertrain.…”
Section: Modeling Of a Light Electric Vehicle Powertrainmentioning
confidence: 99%
“…These speed variations determine the speed and torque to be supplied by the electrical motor. This is done through a throttle sensor, which receives the speed signal operated by the driver and establishes a voltage reference value in the pulse width modulation (PWM) control, to control the desired speed and torque of the motor [24]. The electrical power is provided by a pack of six‐lead acid batteries connected in series, and it is transferred to the mechanical system through a drive axle gearbox, which links the electrical and mechanical power systems in the powertrain.…”
Section: Modeling Of a Light Electric Vehicle Powertrainmentioning
confidence: 99%
“…In Ref. the problem of motor drive control was approached using a HIL platform to develop an emulation‐based virtual laboratory. A very popular approach is to use Lego Mindstorms NXT platforms, such as those presented in .…”
Section: Educational Platforms In Control Engineeringmentioning
confidence: 99%
“…HIL simulation is an emerging technology in the practical learning of power electronics [8]. In Porobic et al [18], Typhoon HIL simulators are used in practical learning for induction motor control. A solar PV test bench based on OPAL‐RT OP4500 is deployed at the University of New South Wales [13], and the students use it as an intermediate step between design and deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Soomro et al [21] reported the HIL application in power electronics courses in Pakistan. In Porobic et al [18], HIL simulation is employed in the practical learning of AC motor control.…”
Section: Introductionmentioning
confidence: 99%